2013
DOI: 10.1094/phyto-10-12-0263-r
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the Population Structure in a Global Collection of Phytophthora nicotianae Isolates Inferred from Mitochondrial and Nuclear DNA Sequences

Abstract: Genetic variation within the heterothallic cosmopolitan plant pathogen Phytophthora nicotianae was determined in 96 isolates from a wide range of hosts and geographic locations by characterizing four mitochondrial (10% of the genome) and three nuclear loci. In all, 52 single-nucleotide polymorphisms (SNPs) (an average of 1 every 58 bp) and 313 sites with gaps representing 5,450 bases enabled the identification of 50 different multilocus mitochondrial haplotypes. Similarly, 24 SNPs (an average of 1 every 69 bp)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…Frequent cases of differential virulence on a range of hosts have been revealed (Colas et al ., ; Matheron and Matejka, ), pointing out the need to decipher the genetic structure of P. parasitica on a global scale. In agreement with pathogenicity tests, recent single nucleotide polymorphism analyses conducted with mitochondrial and nuclear genes have revealed a specific association between the host of origin and genetic grouping which was particularly evident for tobacco and citrus isolates (Mammella et al ., , ). In contrast, no clear genetic structure was revealed for isolates from other hosts, especially potted ornamentals in nurseries.…”
Section: Phytophthora Parasiticamentioning
confidence: 99%
See 1 more Smart Citation
“…Frequent cases of differential virulence on a range of hosts have been revealed (Colas et al ., ; Matheron and Matejka, ), pointing out the need to decipher the genetic structure of P. parasitica on a global scale. In agreement with pathogenicity tests, recent single nucleotide polymorphism analyses conducted with mitochondrial and nuclear genes have revealed a specific association between the host of origin and genetic grouping which was particularly evident for tobacco and citrus isolates (Mammella et al ., , ). In contrast, no clear genetic structure was revealed for isolates from other hosts, especially potted ornamentals in nurseries.…”
Section: Phytophthora Parasiticamentioning
confidence: 99%
“…In contrast, no clear genetic structure was revealed for isolates from other hosts, especially potted ornamentals in nurseries. A significant geographical structuring was revealed for tobacco, but not for citrus, isolates (Bonnet et al ., ; Colas et al ., ; Mammella et al ., ). Further studies relying on whole‐genome sequencing programmes (see below) are necessary to determine whether these molecular groups represent evidence of physiological races, pathotypes or even subspecies within P. parasitica .…”
Section: Phytophthora Parasiticamentioning
confidence: 99%
“…and pinpointed P. nicotianae as the most important species in citrus orchards of other states (4,18). There are conflicting findings concerning intraspecific variability of P. nicotianae from citrus in the literature since 24 citrusinfecting P. nicotianae from India were distributed in different clusters (20), whereas one single clade grouped isolates from Philippines, Italy, Syria, California and Florida (15). The genetic diversity verified in this study contrasting with the high similarity observed by Rosa et al (23) is another case of discrepancy of P. nicotianae (from São Paulo State, this time) and can be credited to different pathogen isolates and a larger number of isolates examined in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nucleotide sequence variation in nuclear and mitochondrial markers revealed an association between crops and genetic groups, suggesting the possibility of host specialization driven by propagation or cultivation practices (Biasi et al ., ). For example, isolates from Citrus were genetically similar, regardless of the country of origin, and genetically differentiated from populations recovered from other hosts (Mammella et al ., , ; Biasi et al ., ). Phytophthora nicotianae from tobacco exhibited clonality within populations (Zhang et al ., ; Parkunan et al ., ), but genetic differentiation among regions (Mammella et al ., , ; Biasi et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, isolates from Citrus were genetically similar, regardless of the country of origin, and genetically differentiated from populations recovered from other hosts (Mammella et al ., , ; Biasi et al ., ). Phytophthora nicotianae from tobacco exhibited clonality within populations (Zhang et al ., ; Parkunan et al ., ), but genetic differentiation among regions (Mammella et al ., , ; Biasi et al ., ). Conversely, isolates from ornamental potted plants presented more genetic variation within populations and less differentiation among host genera and regions (Biasi et al ., ).…”
Section: Introductionmentioning
confidence: 99%